2018
DOI: 10.21089/njhs.34.0139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Foot Care among Diabetic Patients at a Public Tertiary Care Hospital Lahore

Abstract: Background: The diabetic foot complication is further complicated by some UN desired and wrong practices of such as Socio-cultural myths of walking barefoot and religious belief of walking on fire etc. Sometimes inappropriate use of footwear and lack of awareness regarding proper foot care during diabetes mellitus also make the foot complication severe [1].Objective: The specific objectives of this research work are: To assess knowledge of Diabetic foot self -care among patients attending Diabetic clinic at LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Trimming toenails straight can prevent toenails damage (Pourkazemi et al, 2020). However, a multi-centered study in Lahore reported that most of the patients with Diabetes (81.5%) never regularly trimmed their toenails (Akhtar et al, 2018).…”
Section: Foot Care Behavior (Foot Hygiene)mentioning
confidence: 99%
“…Trimming toenails straight can prevent toenails damage (Pourkazemi et al, 2020). However, a multi-centered study in Lahore reported that most of the patients with Diabetes (81.5%) never regularly trimmed their toenails (Akhtar et al, 2018).…”
Section: Foot Care Behavior (Foot Hygiene)mentioning
confidence: 99%
“…Trimming toenails straight can prevent toenails damage (Pourkazemi et al, 2020). However, a multi-centered study in Lahore reported most of the patients with diabetes (81.5%) never trimmed their toenails regularly (Akhtar et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Prevalence of nutritional anemia in children is high in low- and middle-income countries. About 51% of the young children are affected due to nutritional anemia, 2 which is more prevalent in South Asia and Africa. 3 In Pakistan, nutritional anemia has been recognized to be the most common type of anemia in under nourished children.…”
Section: Introductionmentioning
confidence: 99%